Serum Testosterone Level, Testosterone Replacement Treatment, and Prostate Cancer. (18th September 2013) - Atan, Ali; Tuncel, Altug; Yesil, Suleyman; Balbay, Derya
Abstract : There has been an increase in the number of individuals seeking testosterone (T) replacement treatment (TRT) due to a decrease in their blood T levels. Prostate cancer (PCa) is also an important issue in the same age group. However, we, urologists, are anxious about PCa development after T treatment. This is because it has been assumed that T may cause PCa or exacerbate insidious PCa which is already present. In this paper, recent developments regarding the relationship between serum levels of sex hormone and prostate tissue, the causal relationship between T and development of PCa, the effect of TRT on the group of patients who are at high risk of developing PCa, the suitability of TRT for patients who have already been diagnosed with PCa, and the effect of TRT on serum prostate-specific antigen level are analyzed.